Bayberry tannin directed assembly of a bifunctional graphene aerogel for simultaneous solar steam generation and marine uranium extraction. Issue 10 (5th March 2021) - Wu, Fangwu; Liu, Dan; Li, Guangyong; Li, Liqiang; Yan, Lifeng; Hong, Guo; Zhang, Xuetong
Abstract : A bayberry tannin (BT) directed assembly of a bifunctional graphene aerogel (BGA) has been successfully fabricated, which can simultaneously achieve high performance solar steam generation and uranium adsorption capacity. Abstract : Solar steam generation and marine uranium extraction are promising methods for obtaining sufficient fresh water and nuclear fuel from the ocean, respectively, for overcoming water and energy crises. In this work, a bayberry tannin (BT) directed assembly of a bifunctional graphene aerogel (GA) has been designed for simultaneous solar steam generation (1.80 kg m −2 h −1 with a high solar efficiency of 95.5%) and marine uranium extraction (230.10 mg g −1 within 6 h). BT molecules are uniformly decorated inside the typical porous channels of GA, which integrates the excellent uranium binding of BT and the efficient light-to-heat conversion of GA. It is found that the hydrophilic nature of BT can improve fluid infiltration in the GA matrix for solar steam generation while the steam generation induced transpiration can accelerate the adsorption of uranium ions for marine uranium extraction. The unique bifunctional ability of the BT-GA composite paves a new way to utilize the abundant resources in the ocean.